HADIS-HADIS DA’IF PUASA RAMADAN DALAM TAFSIR AL-DUR AL-MANTHUR KARYA AL-SUYUTI - Afif Nurafifah (UIN Siber Syekh Nurjati Cirebon, 2017)
Tafsir al-Dur al-Manthur the only interpretation bi al-Ma’thur pristine history. In general, tafsir bi al-Ma’thur sometimes specifying the hadith is weak in his comments. Fasting has more value than the other worship. So how is the quality of all da’if 's tradition of Ramadan fasting in Tafsir al-Dur al-Manthur and how to use da’if tradition in the view of al-Suyuti and muhaddithin. It aims to identify the quality of all da’if's tradition of Ramadan fasting in Tafsir al-Dur al-Manthur and describe how kehujjahan da’if tradition in the view of al-Suyuti and muhaddithin.